KEMUDAHAN APLIKASI DAN KERAGAMAN PRODUK DALAM MEMBENTUK KEPUTUSAN PEMBELIAN GENERASI MILENIAL BERBELANJA SECARA ONLINE - Awy Apriani Ningrum Simamora; Marlya Fatira (Politeknik Negeri Ambon, 2019)
This research is about the impact given by the availability of Ease of Use of Applications and Kergasan Products sold online to millennial generation purchasing decisions in online shopping. The data used in this study are primary and secondary data. Data collection techniques are questionnaire and literature study. The method used in this research is descriptive analysis, multiple linear regression with t test, f test, correlation coefficient, and determination coefficient. The results showed that the characteristics of millennials who shop online are consumers of the majority of women, aged 20, and the results of this study also show that ease of application and diversity of online products can positively and strongly influence millennial generation purchasing decisions. online purchasing decisions. The ability to influence is indicated by a figure of 47.5% while the remaining 52.5% is influenced by other variables not included in this study.